Language Politeness in the Speech of Cinta Subuh Film Directed by Indra Gunawan - Antika, Aulia Putri; Azizah, Aida (UIR Press, 2024)
This study attempts to describe the principles of politeness that are adhered to and violated in Indra Gunawan's film